الجاحظ مؤلّفاً - زردة يوسف; ديوب هيفاء (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يسلّط البحث الضّوء على الجاحظ (ت 255هـ) بوصفه مؤلّفاً منسجماً مع الحياة بكلّ معانيها , وما كان يشيع فيها, فقد كان صدى ذلك التوثّب والغنى والتنوّع معاً, فهو ليس عالماً طبيعيّاً مجرّداً من الاهتمام بأمور اللغة والدين والأدب والسياسة, وليس لغويّاً انصرف عن الأدب والدين وسواهما, وكذلك ليس فيلسوفاً أو ناقداً انقطع عن الخوض في المفاضلة والفصل بين أهل الفِرَق والمِلل في سياق الدّين والعبادات . بل – كما أشرنا – خاض في كلّ ما ذكرنا معزّزاً مفهوم الأدب في عصره بوصفه الأخذ من كلّ علمٍ بطرف, ولم يكن رأيه مأسوراً تماماً , ولا كلامه مغموراً في علمٍ أو فكرٍ أو لغةٍ وما عدا ذلك كلّه حتّى رأيناه يجمع جمع الراوية , ويجرّب تجريب العالم, ويحلّل تحليل النّاقد , ويُعلي العقل إعلاء الفيلسوف , ثمّ بعد هذا لا يترك الدّين ومذاهب النّاس فيه من غير أن يصف ويقارن ويؤوّل فيفضّل هذا ويؤخّر ذاك , ثمّ يخلط الأوراق فينتج كتباً ورسائل, فيها من كلّ لونٍ وطعمٍ, بنكهة جاحظيّة, و حليةٍ عبّاسيّة مصوغةً صياغةً أدبيّة بأسلوبٍ عذبٍ منسرح . This study focuses on Al-Jahez(255 Hijra) asaharmonious writer with life of all its forms and contents because he was considered the appeal of enthusiasm, richness and difference altogether. However, al-Jahez is neither anatural scientist isolated from caring for language, religion, literature and politics, nor alinguist who ignored literature, religion or anything else. Similarly, he is aphilosopher who didn’t give up dealing with disparity and the difference between communities and groups in the field of religion and worship. He dealt with all that is mentioned above concentrating on the content of literature in his time and making use of every science. Al-Jahez belief wasn’t influenced and his speech wasn’t indulged in a science, alanguage or an ideology. He collected as a narrator, as experienced as ascientist, as analyst as a critic and highly elevating the mind as a philosopher. As for religion and people’s beliefs, he describes, compares, interprets, prefers this to that, then mixes the papers that lead to books and dissertations that disclose a variety of colours and tastes: al-Jahez’s style and Abbaseid image that are well woven as far as the smoothness and fluency of the literary style.